Type I-F CRISPR-Cas resistance against virulent phages results in abortive infection and provides population-level immunity - Bridget N. J. Watson (Nature Portfolio, 2019)
Bacteria use CRISPR-Cas systems to protect themselves against viral infections. Here, Watson et al. show that a type I CRISPR-Cas system can induce abortive viral infection, where infected cells do not survive but viral propagation is decreased, thus protecting the bacterial population.